Case Report: an unusual case of a penetrating intracranial metallic foreign body removed via surgery - Tang, Dang; Song, Hai; Gao, Bibo; Long, Jiang; Ren, Zhongkun (Frontiers in Surgery, 2025)
Background and importanceIntracranial foreign bodies resulting from criminal assaults that cause penetrating trauma are relatively rare. Such cases are often accompanied by significant complications, including intracranial hemorrhage, cerebral contusion, major vascular injury, and cerebrospinal fluid leakage, which pose substantial challenges in clinical management. Herein, we report a successful case of surgical treatment for an intracranial metallic foreign body, aiming to provide valuable insights for similar clinical scenarios.Clinical presentationA 38-year-old male patient was urgently admitted to our emergency department following an intentional assault with a sickle, which resulted in an intracranial penetrating injury. Computed tomography (CT) scanning revealed the presence of a metallic foreign body that traversed the left temporal lobe and extended to the sphenoid bone and the posterior region of the right orbit. In response to this critical situation, an emergency surgical procedure was promptly initiated. The treatment strategy involved a combination of craniotomy and transnasal approaches to remove the metallic foreign body and reconstruct the skull base. Postoperatively, the patient exhibited no obvious adverse reactions, and his condition remained stable throughout the follow-up period.ConclusionIntracranial foreign bodies often penetrate neural structures via the orbit or nasal cavity. When dealing with a long foreign body predominantly situated within the brain parenchyma, it is crucial to avoid blindly extracting it. Instead, shortening the length of the foreign body may be a more feasible approach to facilitate its safe removal and transportation. Preoperative acquisition of comprehensive imaging data is of utmost importance, as it aids in delineating the spatial relationship between the foreign body, major intracranial vessels, and cranial nerves, thereby enabling the formulation of a rational surgical plan. Whenever possible, the removal of intracranial foreign bodies should be carried out within 6–8 h post-trauma. Additionally, reliable skull base reconstruction is essential to prevent cerebrospinal fluid (CSF) leakage and mitigate the risk of infectious complications.